Desiccation Treatment and Endogenous IAA Levels Are Key Factors Influencing High Frequency Somatic Embryogenesis in Cunninghamia lanceolata (Lamb.) Hook - Zhou, Xiaohong; Zheng, Renhua; Liu, Guangxin; Xu, Yang; Zhou, Yanwei; Laux, Thomas; Zhen, Yan; Harding, Scott A.; Shi, Jisen; Chen, Jinhui (Frontiers in Plant Science, 2017)
Cunninghamia lanceolata (Lamb.) Hook (Chinese fir) is an important tree, commercially and ecologically, in southern China. The traditional regenerating methods are based on organogenesis and cutting propagation. Here, we report the development of a high-frequency somatic embryogenesis (SE) regeneration system synchronized via a liquid culture from immature zygotic embryos. Following synchronization, PEM II cell aggregates were developmentally equivalent in appearance to cleaved zygotic embryos. Embryo and suspensor growth and subsequent occurrence of the apical and then the cotyledonary meristems were similar for zygotic and SE embryo development. However, SE proembryos exhibited a more reddish coloration than zygotic proembryos, and SE embryos were smaller than zygotic embryos. Mature somatic embryos gave rise to plantlets on hormone-free medium. For juvenile explants, low concentrations of endogenous indole-3-acetic acid in initial explants correlated with improved proembryogenic mass formation, and high SE competency. Analysis of karyotypes and microsatellites detected no major genetic variation in the plants regenerated via SE, and suggest a potential in the further development of this system as a reliable methodology for true-to-type seedling production. Treatment with polyethylene glycol and abscisic acid were of great importance to proembryo formation and complemented each other. Abscisic acid assisted the growth of embryonal masses, whereas polyethylene glycol facilitated the organization of the proembryo-like structures. SOMATIC EMBRYOGENESIS RECEPTOR KINASE (SERK) and the WUSCHEL homeobox (WOX) transcription factor served as molecular markers during early embryogenesis. Our results show that ClSERKs are conserved and redundantly expressed during SE. SERK and WOX transcript levels were highest during development of the proembryos and lowest in developed embryos. ClWOX13 expression correlates with the critical transition from PEMs to proembryos. Both SERK and WOX expression reveal their applicability in Chinese fir as markers of early embryogenesis. Overall, the findings provided evidence for the potential of this system in high fidelity Chinese fir seedlings production. Also, SE modification strategies were demonstrated and could be applied in other conifer species on the basis of our hormonal, morphological and molecular analyses.